Application of Combined Weighting–Fuzzy Hierarchical Model in Condition Assessment of Concrete Continuous Girder Bridges - Jiali Yue; Hailin Lu; Rusheng Qian; Jun Tang (Buildings)
To solve the problem of state evaluations of small- and medium-span bridges such as concrete continuous girder bridges, this paper developed an extended model based on game theory. Aiming at Nash equilibrium, the combined weighting–fuzzy hierarchical comprehensive evaluation model was constructed by the combination of the analytic hierarchy process and the entropy weight method, which was corrected using the BP neural network. A three-span prestressed concrete continuous girder bridge in Wuhan was evaluated using health monitoring data and manual inspection information and compared to the results obtained using the traditional methods. The evaluation results showed that the error between the first-order frequency and the measured frequency was reduced from 17.95% to 9.00% and the bridge’s overall state score was 89.72. The evaluation model constructed by the method in this paper can take into account the contents of health monitoring and manual detection and coordinate the subjective and objective weights. Compared to the results of the analytic hierarchy process model and the fuzzy comprehensive evaluation model, the proposed model is reliable and applicable.